KECERNAAN RANSUM SAPI PERANAKAN ONGOLE BERBASIS LIMBAH PERKEBUNAN KELAPA SAWIT YANG DIAMONIASI UREA - Dewi Febrina (Jurnal Peternakan, 2012)
The utilization of palm plantation waste as feed is constrained because of its high fiber and anti nutrition content, also lower protein content. The treatment of ammoniated palm plantation waste with long period of harvest for 7 days give the best result based on the dried content and lower fiber content. The purpose of this research is to determine the effect of different frequency of feed to the dry matter intake, crude fiber, crude protein and crude fat of Ongole crossbreed cattle based on palm plantation waste feed ammoniated by urea. This research was conducted by an in - vitro method for 135 days, included 15 days of adaptation period and 120 days of data collecting. The method use in this research was Latin square 4 x 4. The treatment was different feed frequency, A = ad libitum feed, B = the feeding frequency gave twice in a day, C = the feeding frequency gave three times in a day, and D = the feeding frequency gave four times in a day. The result showed that the feeding frequency did not significantly affect (P>0,05) to dry matter intake, crude fiber, crude protein and crude fat content of Ongole crossbreed feed based on oil plantation waste ammoniated by urea